Carnosine decreases IGFBP1 production in db/db mice through suppression of HIF-1 - Forsberg, Elisabete; Peters, Verena (The journal of endocrinology, 2015)
IGF binding protein 1 (IGFBP1) is a member of the binding proteins for the IGF with an important role in glucose homeostasis. Circulating IGFBP1 is derived essentially from the liver where it is mainly regulated negatively by insulin. Carnosine, a natural antioxidant, has been shown to improve metabolic control in different animal models of diabetes but its mechanisms of action are still not completely unraveled. We therefore investigate the effect of carnosine treatment on the IGFBP1 regulation in db/db mice. Db/db mice and heterozygous non-diabetic mice received for 4 weeks regular water or water supplemented with carnosine. lgfbp1 mRNA expression in the liver was evaluated using qPCR and the protein levels in plasma by western blot. Plasma IGF1 and insulin were analyzed using immunoassays. HepG2 cells were used to study the in vitro effect of carnosine on IGFBP1. The modulation of hypoxia inducible factor-1 alpha (HIF-1α) which is the central mediator of hypoxia-induction of IGFBP1 was analyzed using: WB, reporter gene assay and qPCR. Carnosine decreased the circulating IGFBP1 levels and the liver expression Igfbp1, through a complex mechanism acting both directly by suppressing the HIF-1α-mediated IGFBP1 induction and indirectly through increasing circulating insulin level followed by a decrease in the blood glucose levels and increased the plasma levels or IGF1. Reduction of IGFBP1 in diabetes through insulin-dependent and insulin-independent pathways is a novel mechanism by which carnosine contributes to the improvement of the metabolic control in diabetes.
Gesehen am 04.08.2021